Enhancing Public Trust in Zakat Institutions Through Transparency of Zakat Fund Management - KMT Lasmiatun (UIN Siber Syekh Nurjati Cirebon, 2020)
This study aims to examine the role of transparency in zakat fund management in enhancing public trust in zakat institutions. Transparency is considered a critical factor in strengthening institutional credibility, particularly in Islamic philanthropic organizations where accountability and trust are essential for sustainability. This research employs a mixed-method approach, combining quantitative data analysis and qualitative insights to provide a comprehensive understanding of the relationship between transparency practices and public trust. The quantitative data were collected through structured questionnaires distributed to zakat contributors, while qualitative data were obtained through in-depth interviews with stakeholders in zakat institutions. The findings indicate that transparency in financial reporting, information disclosure, and governance practices significantly influences public trust. Institutions that provide clear, accessible, and timely information regarding the collection, allocation, and utilization of zakat funds tend to gain higher levels of trust from the public. Furthermore, the study highlights that transparency not only improves accountability but also encourages greater participation in zakat contributions. This study contributes to the literature by emphasizing the strategic importance of transparency as a key determinant of trust in zakat institutions. It also provides practical implications for policymakers and zakat managers to enhance governance systems and adopt transparent practices in order to strengthen public confidence and ensure the long-term sustainability of zakat institutions.